Successful Allogeneic Neonatal Bone Marrow Transplantation Devoid of Myeloablation Requires Costimulatory Blockade - Soper, Brian W; Lessard, Mark D; Jude, Craig D; Schuldt, Adam J. T; Bunte, Ralph M; Barker, Jane E (The Journal of immunology (1950), 2003)
A significant number of nonmalignant, progressive childhood disorders respond to bone marrow transplantation (BMT). Toxic myeloablative pretreatment regimens, graft failure, and graft-vs-host disease complicate the utility of BMT for neonatal treatment. We recently demonstrated high-dose BMT in neonatal animals enables chimeric engraftment without toxic myeloablation. Reagents that block T cell costimulation (anti-CD40L mAb and/or CTLA-4Ig) establish tolerant allogeneic engraftment in adult recipients. Donor lymphocyte infusion (DLI) re-establishes failing grafts and treats malignant relapse via a graft-vs-leukemia response. In this study, we tested the hypothesis that combining these approaches would allow tolerant allogeneic engraftment devoid of myeloablation in neonatal normal and mutant mice with lysosomal storage disease. Tolerant chimeric allogeneic engraftment was achieved before DLI only in the presence of both anti-CD40L mAb and CTLA-4Ig. DLI amplified allografts to full donor engraftment long-term. DLI-treated mice either maintained long-term tolerance or developed late-onset chronic graft-vs-host disease. This combinatorial approach provides a nontoxic method to establish tolerant allogeneic engraftment for treatment of progressive childhood diseases.